2003
DOI: 10.1074/jbc.m211379200
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the Calcitonin Gene-related Peptide Receptor Complex at the Vertebrate Neuromuscular Junction and Its Role in Regulating Acetylcholinesterase Expression

Abstract: The calcitonin gene-related peptide (CGRP) is released by motor neurons where it exerts both short and long term effects on skeletal muscle fibers. In addition, sensory neurons release CGRP on the surrounding vasculature where it is in part responsible for local vasodilation following muscle contraction. Although CGRPbinding sites have been demonstrated in whole muscle tissue, the type of CGRP receptor and its associated proteins or its cellular localization within the tissue have not been described. Here we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 68 publications
1
42
0
Order By: Relevance
“…In contrast with the results of the knock-out study, emerging lines of evidence suggest that CGRP is still an excellent candidate to be a neuron-derived factor in directing the formation and/or the maintenance of postsynaptic specializations, in particular the regulation of AChE in muscle. Several studies have suggested an AChE-regulating role for CGRP in muscle, including the regulation of AChE T in rodents (14) and chickens (13), the induction of ColQ mRNA (23), the modification of AChE molecular forms (32), and the suppression of PRiMA (Fig. 6) and G 4 AChE (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast with the results of the knock-out study, emerging lines of evidence suggest that CGRP is still an excellent candidate to be a neuron-derived factor in directing the formation and/or the maintenance of postsynaptic specializations, in particular the regulation of AChE in muscle. Several studies have suggested an AChE-regulating role for CGRP in muscle, including the regulation of AChE T in rodents (14) and chickens (13), the induction of ColQ mRNA (23), the modification of AChE molecular forms (32), and the suppression of PRiMA (Fig. 6) and G 4 AChE (31).…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with the fact that CGRP induced CREB phosphorylation. The CGRP-induced CREB phosphorylation is mediated by a cAMP-dependent signaling pathway, via a CGRP receptor complex on the muscle surface (15,32). In contrast, the mechanism of muscular activity-induced CREB phosphorylation has not yet been determined.…”
Section: Regulation Of G 4 Ache and Prima During Myogenicmentioning
confidence: 99%
“…Of these, CGRP is of special interest because this 37‐amino acid neuropeptide has been found in large dense‐core vesicles (LDCVs) in mammalian motor nerve terminals (Csillik et al., 1993; Matteoli et al., 1988) and is reported to be released as a co‐transmitter in response to sustained depolarization or intense nerve stimulation (Sakaguchi, Inaishi, Kashihara, & Kuno, 1991; Sala, Andreose, Fumagalli, & Lømo, 1995; Uchida et al., 1990) providing the wide spectrum of acute and neurotrophic influences (Buffelli, Pasino, & Cangiano, 2001; Changeux, Duclert, & Sekine, 1992; Correia‐de‐Sá & Ribeiro, 1994; Fernandez, Ross, & Nadelhaft, 1999; Kimura, Okazaki, & Nojima, 1997; Machado et al., 2016; Rossi, Dickerson, & Rotundo, 2003; Salim, Dezaki, Tsuneki, Abdel‐Zaher, & Kimura, 1998). Possible release of endogenous CGRP in response to ryanodine application at resting motor synapses and acute physiological consequences of this release on quantal ACh secretion have not been described yet.…”
Section: Introductionmentioning
confidence: 99%
“…CGRP is present in motor nerve terminals and is released in an activity-dependent manner (22). Production of cAMP and activation of PKA are induced upon CGRP receptor binding, leading to short-and long-term effects (22): CGRP leads to AChR phosphorylation (23), increased AChR (20,24) and decreased acetylcholine esterase expression (25,26), and NMJ-strength potentiation (27). Thus, CGRP seems to be a trophic factor for the NMJ by local stimulation of cAMP signaling.…”
mentioning
confidence: 99%